2016
DOI: 10.1088/1361-6528/28/5/054002
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and atomic manipulation mediated by electronic excitation of the underlying Si(111)-7x7 surface

Abstract: We report the local atomic manipulation properties of chemisorbed toluene molecules on the Si(111)-7x7 surface and of the silicon adatoms of the surface. Charge injected directly into the molecule, or into its underlying bonding silicon adatom, can induce the molecule to change bonding site. The voltage dependence of the rates of these processes match closely with scanning tunnelling spectroscopy of the toluene and adatom species. The branching ratio between toluene molecules which are moved to a neighbouring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 54 publications
2
20
0
Order By: Relevance
“…As we demonstrated in an earlier work the actual molecular displacement is in fact driven by excitation of the underlying silicon surface [27]. It is possible to manipulate the silicon adatoms of the surface in exactly the same fashion as reported here for the toluene adsorbates [40,41].…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…As we demonstrated in an earlier work the actual molecular displacement is in fact driven by excitation of the underlying silicon surface [27]. It is possible to manipulate the silicon adatoms of the surface in exactly the same fashion as reported here for the toluene adsorbates [40,41].…”
Section: Discussionsupporting
confidence: 54%
“…The U 3 state centred at (+2.3±0.5) eV has a clear amplitude at each adatom site. The minimum energy required to manipulate a toluene molecule is +1.4 eV [22,27], and the energy range of photons detectable by our camera is ≈1.4 to 3.1 eV. Thus, we would be insensitive to any transition between the bottom of the U 3 state and next state, U 2 , observed at +1.3 V in the STS (ΔE=0.7 eV).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In addition to the diffusive hole transport, a region near to the injection site (<15 nm) was identified where a ballistic hole transport leads to a substantial reduction of the reaction probability, which one would expect from a purely diffusive model. Furthermore, it was demonstrated that the hole-induced desorption is connected to a surface silicon adatom excitation [31]. For the thermally activated electron-induced desorption of chlorobenzene in Ref.…”
Section: Introductionmentioning
confidence: 98%
“…Thresholds for the bias voltage of 1.4 eV (electrons) and −1.2 eV (holes) have been determined. Further, it was found that the electron induced process is most probably connected to an excitation of the so called silicon ad‐atom . This is in line with earlier experiments reporting an ad‐atom displacement on the Si(111)‐7 × 7 surface for positive bias voltages in the STM manipulation.…”
Section: Introductionmentioning
confidence: 99%